Oxidized LDL and the metabolic syndrome. (December 2008) - Holvoet, Paul; De Keyzer, Dieuwke; Jacobs Jr, David R
The metabolic syndrome is a common and complex disorder combining obesity, dyslipidemia, hypertension and insulin resistance. It is associated with a high cardiovascular risk that can only partially be explained by its components. There is evidence that low-grade inflammation and high oxidative stress add to this risk. Oxidized LDL, a marker of lipoprotein-associated oxidative stress, is an emerging cardiovascular risk factor. In this review, we demonstrate that the metabolic syndrome exacerbates oxidized LDL in a feedback loop. We introduce molecular mechanisms underlying this loop. Finally, we demonstrate that weight loss and statin treatment lower metabolic syndrome factors associated with a reduction of oxidized LDL. The current data warrant further investigation into the role of lifestyle and therapeutic interventions that inhibit tissue-associated oxidation of LDL in the prevention of the metabolic syndrome.